Morphometric and biochemical features of different Bunias orientalis L. genotypes in the M. M. Gryshko National Botanical Garden of the NAS of Ukraine - O. M. Vergun; D. B. Rakhmetov; O. V. Shymanska; S. O. Rakhmetova; O. P. Bondarchuk; V. V. Fishchenko (Plant Varieties Studying and Protection)
Purpose. Determine a number of morphometric and biochemical parameters of various genotypes of Bunias orientalis L. in the M. M. Gryshko National Botanical Garden of the NAS of Ukraine (NBG).